CLIMATE AND MENOPAUSE: NURSING ASSISTANCE FOR WOMEN IN PRIMARY HEALTH CARE - Eduarda Almeida de Souza, Cicera; Denilson Aurélio Soares, Cicero; da Silva Caetano, Belkise; Alves Dantas, Bárbara; Silva Sousa, Natália; Cristina Alves da Silva Lima, Hellen; Dionísio de Almeida, Pâmela; Henrique de Sousa Ribeiro, José; Barros de Quental, Ocilma (Health and Society, 2022)
Introduction: Climacteric and menopause is defined by the World Health Organization as a biological phase of a woman’s life and not a pathological process. have the most severe symptoms. Primary Health Care is the most comprehensive unit in care and women tend to look for the service, for this it is essential that the nursing professional knows signs and symptoms of climacteric and menopause so that a service of assistance to climacteric women can be traced. aiming to guarantee the quality of life in the female aging process. Objective: To identify in the literature the assistance and strategies carried out by nursing in Primary Health Care regarding the care of women in the climacteric and menopause period. Methodology: This is an integrative literature review of a descriptive-exploratory nature, carried out in the scientific databases of the electronic libraries SCIELO, MEDLINE, LILACS and BDENF. Results and Discussions: For this assistance to happen effectively, it is essential that the nursing professional act in the reception of climacteric women who seek the service. Nurses need to adopt care strategies according to the female demand index, as well as health education actions on this climacteric and menopause phase and their respective forms of treatment. Conclusion: There is a need for nursing consultations in PHC aimed at early screening of climacteric and menopause, as well as promoting health education on the aforementioned phases.